Mechanistic insights into the oxidative dissolution and structural transformation of humic acid in carbonaceous gold ores under pressure oxidation - Yue Qi; Hongying Yang; Linlin Tong; Huiqun Niu; Shiqi Zhang (Minerals Engineering, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

A first quantitative assessment of seabed litter collection efficiency using bottom otter trawls and fishery depletion models - Yue Chen; Xinxing You; Linlin Gao; Huaxiang Sheng; Yipu Sui; Xinle Xu; Liuyi Huang (Environmental Pollution, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Development and application of a numerical model of an asynchronized parallel double-stage fluid viscous damper for seismic responses control based on OpenSees - Linlin Xie; Haoxiang Wang; Cantian Yang; Aiqun Li; Yue Chen (Engineering Structures, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Atmospheric boundary layer heat budget and its urban-rural differences in Beijing during a heatwave event - Qianyue Huang; Yuanjie Zhang; Jialing Xin; Yubin Li; Yue Qin; Linlin Wang (Atmospheric Research, 2025)

Integrated transcriptome and metabolome analyses reveal regulatory mechanisms governing carbohydrate biosynthesis in Panax ginseng - Qiao Jin; Qiuxia Wang; Linlin Zhang; Yue Zhang; Zhengbo Liu (Plant Science, 2025)

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Study on complex failure modes of super-long piles in deep-water and soft-clay seabed under multiple combined loads - Linlin He; Xuan Liu; Yuanshi Xie; Shuting Cao; Yue Liang; Yang Liu (Ocean Engineering, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

One-step synthesis of K3PO4-activated phosphorus-enriched carbons for enhanced carbon capture - Yue Zhi; Yujia Yin; Quji Ciren; Qiang Xiao; Leihong Zhao; Muslum Demir; Utku Bulut Simsek; Xin Hu; Linlin Wang (Journal of Environmental Chemical Engineering, 2025)

Glycyrrhizic acid alleviates gefitinib-induced liver injury by regulating the p53/p21 pathway and releasing cell cycle arrest - Min Li; Shuaijun Peng; Jingjing Bu; Siqi Quan; Liming Liu; Zhouli Yue; Linlin Wang; Yucheng Li (Food and Chemical Toxicology, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

Tailoring carbon intercalated α,β-FePc heterophase junction to boost electron transfer for 1O2-dominated photo-Fenton reaction - Zhiling Du; Cailiang Yue; Linlin Zhu; Changqing Zhu; Qing Du; Fuqiang Liu (Chemical Engineering Journal, 2024)

Biomass-derived carbon dots with pharmacological activity for biomedicine: Recent advances and future perspectives - Yue Liu; Linlin Zhang; Huijuan Cai; Xiaoli Qu; Junbiao Chang; Geoffrey I.N. Waterhouse; Siyu Lu (Science Bulletin, 2024)

Degradation of mycotoxins by pulsed light and evaluation of the safety of degradation products - Lige Qi; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang; Xubo Zhao (Journal of Food Engineering, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Anti-cancer effects of nitazoxanide in epithelial ovarian cancer in-vitro and in-vivo - Xiangqun Yang; Zhenyan Liu; Xin Wang; Wenda Tian; Taoyu Zhao; Qiaoling Yang; Wenliang Li; Linlin Yang; Hongying Yang; Yue Jia (Chemico-Biological Interactions, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Microbiological hazards in infant and toddler food in China: A comprehensive study between 2004 and 2022 - Lin Teng; Linlin Huang; Haiyang Zhou; Baikui Wang; Min Yue; Yan Li (Food Research International, 2024)

How the subsurface wastewater infiltration systems with iron‑carbon micro-electrolytic substrate achieve high pollutants removal: A metabolomic view - Yinghua Li; Linlin Peng; Yiyan Wang; Yue Zhang; Fei Su; Jie Qian (Journal of Water Process Engineering, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Cloning and expression of the mitochondrial cytochrome c oxidase subunit II gene in Sitophilus zeamais and interaction mechanism with allyl isothiocyanate - Linlin Jiang; Yue Li; Weilin Shi; Wei Chen; Zhiqing Ma; Juntao Feng; Ahmed S. Hashem; Hua Wu (Pesticide Biochemistry and Physiology, 2023)

Recent advances of plasmonic elemental Bi based photocatalysts in environmental remediation and energy conversion - Cailiang Yue; Linlin Zhu; Yixing Qiu; Zhiling Du; Jinli Qiu; Fuqiang Liu; Fenghe Wang (Journal of Cleaner Production, 2023)

Seismic performance of precast concrete frame with energy dissipative cladding panel system: Half-scale test and numerical analysis - Huiling Sha; Xun Chong; Linlin Xie; Pu Huo; Tengsheng Yue; Jianpeng Wei (Soil Dynamics and Earthquake Engineering, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Prenatal exposure to silver is associated with an elevated risk for neural tube defects: a case–control study - Xin Pi; Chengrong Wang; Di Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Wentao Yue; Chenghong Yin; Aiguo Ren (Environmental Science and Pollution Research, 2022)

High levels of serum IL-10 indicate disease progression, extramedullary involvement, and poor prognosis in multiple myeloma - Xiaoyan Yue; Linlin Huang; Yang Yang; Yi Zhao; Donghua He; Xiaoyan Han; Gaofeng Zheng; Yi Li; Enfan Zhang; Zhen Cai; Xin Huang; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Wei Zhang; Yue Xu; Yu Xue; Linlin Zhang (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate . We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.

Taxonomy and regeneration of a newly recorded Polychaete Capitella teleta (Annelida, Capitellidae) in the coastal water of Shandong, China - Qian Li; Yongnan Li; Yue Wang; Xuwen Wu; Linlin Zhang (Journal of Oceanology and Limnology, 2022)

Creep characteristics and prediction of creep failure of rock discontinuities under shearing conditions - Zhen Wang; Linlin Gu; Qingzhao Zhang; Songlin Yue; Guokai Zhang (International Journal of Earth Sciences, 2020)

Integrated space geodesy for mapping land deformation over Choushui River Fluvial Plain, Taiwan - Linlin Ge; Alex Hay-Man Ng; Zheyuan Du; Horng-Yue Chen; Xiaojing Li (International Journal of Remote Sensing, 2017)

A lncRNA promotes myoblast proliferation by up-regulating GH1 - Yingwei Yue; Congfei Jin; Mingming Chen; Linlin Zhang; Xinfeng Liu; Wenzhi Ma; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Characterization of harpinXoo induced hypersensitive responses in non host plant, tobacco - Linlin Xie; Yue Liu; Hui Wang; Wenbo Liu; Rong Di; Weiguo Miao; Fucong Zheng (Journal of Plant Biochemistry and Biotechnology, 2017)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

Integrated Approach Based on a Regional Habitat Succession Model to Assess Wetland Landscape Ecological Degradation - Linlin Cui; Guosheng Li; Huajun Liao; Ninglei Ouyang; Yue Zhang (Wetlands, 2015)

Study on Evolution Features and Spatial Distribution Patterns of Coastal Wetlands in North Jiangsu Province, China - Huajun Liao; Guosheng Li; Linlin Cui; Ninglei Ouyang; Yue Zhang; Shaohua Wang (Wetlands, 2014)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Isolation of two novel complete Ty1-copia retrotransposons from apple and demonstration of use of derived S-SAP markers for distinguishing bud sports of Malus domestica cv. Fuji - Guiling Zhao; Hongyan Dai; Linlin Chang; Yue Ma; Haiyue Sun; Ping He; Zhihong Zhang (Tree Genetics & Genomes, 2010)

MicroRNA expression profiles in conventional and micropropagated strawberry (Fragaria × ananassa Duch.) plants - He Li; Zhihong Zhang; Feifei Huang; Linlin Chang; Yue Ma (Plant Cell Reports, 2009)